N-Nitrosation in the absence of nitrosating agents in pharmaceuticals - Jireš, Jakub; Douša, Michal; Gibala, Petr; Kubelka, Tomáš (Journal of pharmaceutical and biomedical analysis, 2022)
The possibility of N-Nitrosation in the absence of nitrosating agents was studied on model solutions and film coated tablets containing metformin. N-nitrosodimethylamine (NDMA) and N-nitrosation precursors (dimethylamine and nitrites) were determined using previously published fully validated analytical methods. Alternative routes to N-nitrosation were found. Dimethylamine can undergo an oxidation to nitrite in the presence of strong oxidants (e.g., H2O2), as was observed during wastewater treatment in several published works. The resulting nitrite can consecutively act as a nitrosating agent. We proved that the described reaction indeed leads to N-nitrosation (NDMA formation in case of dimethylamine precursor) in model solutions made of dimethylamine and H2O2. An experiment was designed in order to prove those reactions take place in dosage forms. Film coated tablets present a highly heterogenous system with several solid phases and low water activity, which is in stark contrast to the liquid wastewater, where this reaction was originally studied. Despite that, the described reaction took place even in the tablets, but only to a small degree. The amount formed via this alternative route corresponds to less than 10 % of the total formed NDMA. The pH optimum of this alternative route lies in the alkaline range which was confirmed by the determined NDMA concentration in model solutions. The solid phase system (i.e., tablets) was found to behave differently. The addition of Na2CO3 into the tablets during manufacture resulted in tablets without NDMA (cNDMA < LOQ) even in batches spiked with both dimethylamine and H2O2. Thus, adjusting the pH of the solid dosage forms remains a sufficient measure of controlling N-nitrosamines in the product, even in product with limit amounts of oxidating agent (H2O2) and N-nitrosation precursor (dimethylamine).
Keywords: nitrosace; Nitrites; dimethylnitrosamin; léčivé přípravky; dimethylaminy; Dimethylamines; peroxid vodíku; Hydrogen Peroxide; Nitrosation; Pharmaceutical Preparations; dusitany; Dimethylnitrosamine